Assessment on the Challenges Encountered by Academic Librarians on Information Literacy Instruction in Federal Colleges of Education in North-West Geo-Political Zone of Nigeria - John Dada, Kayode Sunday; Atte, Sadiat Lola (Information Research Communications, 2025)
Aims/Background This study aimed to investigate the challenges faced by Academic Librarians in delivering information literacy instruction in Federal Colleges of Education within the North-West Geo-Political Zone of Nigeria. Methodology A quantitative research methodology was employed, utilizing a Cross-Sectional Survey research method. The study adopted a total enumeration sampling technique, where the entire population of Academic Librarians with teaching responsibilities served as the sample. Data were collected using a self-developed closed-ended questionnaire based on the Association of College and Research Libraries (2015) Framework for Information Literacy for Higher Education Standards and Julien, Gross, and Latham (2018) Survey of Information Literacy Instruction Practices in U.S. Academic Libraries. The data were analyzed using descriptive statistics, including Frequency Distribution Tables, percentages, mean, and standard deviation. Results The findings identified several challenges encountered by Academic Librarians in teaching information literacy, including insufficient faculty training and support programs, apathy of staff and students toward Information Literacy Programs, inadequate collaboration between librarians and faculty in information literacy activities, poor awareness among Academic Librarians of their roles in information literacy instruction, and inconsistent teaching styles. Conclusion The study recommends increased faculty engagement and collaboration through symposiums, workshops, and seminars to enhance the delivery of information literacy instruction. Faculty-librarian collaboration should be considered a critical component of the methodology to support student learning, as it can significantly improve the effectiveness of information literacy programs and better equip students and faculty with essential skills for success in the information age.
Keywords: Academic Librarians; Federal Colleges of Education; information literacy instruction; Challenges; Nigeria; North-West Geo-Political Zone